IgA and IgG1 Specific to Vi Polysaccharide of Salmonella Typhi Correlate With Protection Status in a Typhoid Fever Controlled Human Infection Model - Dahora, Lindsay C.; Jin, Celina; Spreng, Rachel L.; Feely, Frederick; Mathura, Ryan; Seaton, Kelly E.; Zhang, Lu; Hill, Jennifer; Jones, Elizabeth; Alam, S. Munir; Dennison, S. Moses; Pollard, Andrew J.; et al. (Frontiers in Immunology, 2019)
Vaccination against Salmonella Typhi using the Vi capsular polysaccharide, a T-cell independent antigen, can protect from the development of typhoid fever. This implies that antibodies to Vi alone can protect in the absence of a T cell-mediated immune response; however, protective Vi antibodies have not been well characterized. We hypothesized that variability in the biophysical properties of vaccine-elicited antibodies, including subclass distribution and avidity, may impact protective outcomes. To interrogate the relationship between antibody properties and protection against typhoid fever, we analyzed humoral responses from participants in a vaccine efficacy trial using a controlled human infection model (CHIM) who received either a purified Vi polysaccharide (Vi-PS) or Vi tetanus toxoid conjugate (Vi-TT) vaccine followed by oral challenge with live S. Typhi. We determined the avidity, overall magnitude, and vaccine-induced fold-change in magnitude from before immunization to day of challenge of Vi IgA and IgG subclass antibodies. Amongst those who received the Vi-PS vaccine, Vi IgA magnitude (FDR p=0.01) and fold-change (FDR p=0.02) were significantly higher in protected individuals compared with those individuals who developed disease (“diagnosed”). In the Vi-TT vaccine group, the responses of protected individuals had higher fold-change in Vi IgA (FDR p=0.06) and higher Vi IgG1 avidity (FDR p =0.058) than the diagnosed Vi-TT vaccinees, though these findings were not significant at p<0.05. Specifically, IgA2 was higher in protected versus diagnosed Vi-PS vaccinees, while IgA1 fold-change and IgA2 avidity were higher in protected versus diagnosed Vi-TT vaccinees. Overall, avidity maturation of all antibody subclasses was higher in the Vi-TT group compared with recipients of Vi-PS; however, avidity of Vi-specific Ig did not increase further following oral challenge with S. Typhi. We conclude that although the Vi-PS and Vi-TT vaccines were observed to have similar efficacies, these vaccines may protect through different mechanisms. Vi IgA magnitude and fold-change correlated with protection status in Vi-PS vaccinees. However, in Vi-TT vaccinees, IgG1 avidity also contributed to the differences in protection status in addition to IgA measures. These data will inform studies on mechanisms of protection against typhoid fever, including identification of antibody effector functions, as well as informing future vaccination strategies.